Preclinic Group Education Sessions Reduce Waiting Times and Costs at Public Pain Medicine Units - Davies, S.; Quintner, J.; Parsons, Richard; Parkitny, L.; Knight, P.; Forrester, E.; Roberts, M.; Graham, C.; Visser, E.; Antill, T.; Packer, Tanya; Schug, S. (Wiley-Blackwell Publishing, Inc, 2011)
Objective. To assess the effects of preclinic group education sessions and system redesign on tertiary pain medicine units and patient outcomes. Design. Prospective cohort study. Setting. Two public hospital multidisciplinary pain medicine units. Patients. People with persistent pain. Interventions. A system redesign from a “traditional” model (initial individual medical appointments) to a model that delivers group education sessions prior to individual appointments. Based on Patient Triage Questionnaires patients were scheduled to attend Self-Training Educative Pain Sessions (STEPS), a two day eight hour group education program, followed by optional patient-initiated clinic appointments. Outcome Measures. Number of patients completing STEPS who subsequently requested individual outpatient clinic appointment(s); wait-times; unit cost per new patient referred; recurrent health care utilization; patient satisfaction; Global Perceived Impression of Change (GPIC); and utilized pain management strategies. Results. Following STEPS 48% of attendees requested individual outpatient appointments. Wait times reduced from 105.6 to 16.1 weeks at one pain unit and 37.3 to 15.2 weeks at the second. Unit cost per new patient appointed reduced from $1,805 Australian Dollars (AUD) to AUD$541 (for STEPS). At 3 months, patients scored their satisfaction with “the treatment received for their pain” more positively than at baseline (change score = 0.88; P = 0.0003), GPIC improved (change score = 0.46; P < 0.0001) and mean number of active strategies utilized increased by 4.12 per patient (P = 0.0004). Conclusions. The introduction of STEPS was associated with reduced wait-times and costs at public pain medicine units and increased both the use of active pain management strategies and patient satisfaction.